A Systematic Review Evaluating Neuraxial Morphine and Diamorphine-Associated Respiratory Depression After Cesarean Delivery. (December 2018) - Sharawi, Nadir; Carvalho, Brendan; Habib, Ashraf S.; Blake, Lindsay; Mhyre, Jill M.; Sultan, Pervez
Abstract : The prevalence of neuraxial opioid–induced clinically significant respiratory depression (CSRD) after cesarean delivery is unknown. We sought to review reported cases of author-reported respiratory depression (ARD) to calculate CSRD prevalence. A 6-database literature search was performed to identify ARD secondary to neuraxial morphine or diamorphine, in parturients undergoing cesarean delivery. "Highest" (definite and probable/possible) and "lowest" (definite) prevalences of CSRD were calculated. Secondary outcomes included: (1) prevalence of CSRD associated with contemporary doses of neuraxial opioid, (2) prevalence of ARD as defined by each study's own criteria, (3) case reports of ARD, and (4) reports of ARD reported by the Anesthesia Closed Claims Project database between 1990 and 2016. We identified 78 articles with 18, 455 parturients receiving neuraxial morphine or diamorphine for cesarean delivery. The highest and lowest prevalences of CSRD with all doses of neuraxial opioids were 8.67 per 10, 000 (95% CI, 4.20–15.16) and 5.96 per 10, 000 (95% CI, 2.23–11.28), respectively. The highest and lowest prevalences of CSRD with the use of clinically relevant doses of neuraxial morphine ranged between 1.63 per 10, 000 (95% CI, 0.62–8.77) and 1.08 per 10, 000 (95% CI, 0.24–7.22), respectively. The prevalence of ARD as defined by each individual paper was 61 per 10, 000 (95% CI, 51–74). One published case report of ARD met our inclusion criteria, and there were no cases of ARD from the Closed Claims database analysis. These results indicate that the prevalence of CSRD due to neuraxial morphine or diamorphine in the obstetric population is low. Abstract : Supplemental Digital Content is available in the text.